Implementation of a methodology for consideration of product quality within discrete manufacturing - Foehr, Matthias (2014)
The present paper deals with the questions how product quality can be influenced within product manufacturing and how production control can be optimized for increasing product quality. It focuses on discrete manufacturing processes and presents a methodology to gather and analyze relevant influences on product quality and a multi-agent architecture for flexible and quality focused production control. It will be shown how both approaches can be implemented to achieve a flexible, adaptable and quality focused production process control.